Possible relation between psychosis and the unconscious: a review of “The Unconscious,” by Freud - de Oliveira Moreira, Jacqueline; Drawin, Carlos R. (Frontiers in Psychology, 2015)
This reviewintends to present some elements of the Freudian thinking on psychosis, focusing on the relations between psychosis and the unconscious. The unconscious phenomena which episodically cross the neurotic individual are massively and continuously shown on psychosis. The psychotic individual appears to be constantly invaded by the other, like a strange person, which bursts inside of him/her and presents itself as a threat to the process of construction of this person’s identity. But what is the relation between the unconscious and psychosis in the Freudian text? It could be concluded that the psychotic individual may be invaded by a pulsating unconscious which demands a symbolic mediation. This reveals the importance of associating verbal construction tomedication in cases of psychosis.